O policial militar aposentado e o retorno ao trabalho institucional - Nunes, Régis Brum (2016)
The military professionals of Rio Grande do Sul state rely with a law that support their voluntary return to the corporation after retirement. A significant number of professionals have joined to this possibility. The study aims to identify the reason that make part of the military police officers return to the police work after obtaining the retirement, the characteristics of the work process, their habits and the self-perception of health. The study of descriptive and transversal type has a population of 120 Military Police Officers from Regional Command Ostensive Police of the Planalto, with headquarters in Passo Fundo (RS), belonging to the Voluntary Staff of Inactive Military in the Military Police. The collection of data included relevant issues to four previous categories of analysis, that are: sociodemographic characteristics and personal; profile of work, retirement and rent; perception of work, retirement and return; and habits and self-perception of health. The data were treated by means of simple descriptive statistics, such as the analysis of frequency, correlation and crossed tabulation. The first production of the dissertation had the intention of identify the reasons that make part of the military police officers return to police work after obtaining the retirement. The results of this production have pointed out that the main reason for return to the institution is related to the need to feel useful and productive and identification with the profession showed as an important component of motivation. Other two productions, in the conclusion phase, focus on the military police work and the techniques of human resources adopted by the institution and, second, the self-perception of health of military police retirees who had returned to the institutional work